2015
DOI: 10.1016/j.metabol.2014.10.018
|View full text |Cite
|
Sign up to set email alerts
|

Effect of lifestyle intervention in patients with type 2 diabetes: A meta-analysis

Abstract: The meta-analysis found that lifestyle intervention showed significant benefit in risk factors that are known to be associated with development of cardiovascular disease in patients with type 2 diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
198
1
17

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 274 publications
(232 citation statements)
references
References 28 publications
16
198
1
17
Order By: Relevance
“…To date, lifestyle intervention including pharmacological management (Table 5) and bariatric surgery in morbidly obese patients have demonstrated greatest efficacy in delaying/preventing diabetes onset in pre-diabetic individuals, achievement of glycemic control and improvement in oral indices. 65 In the absence of screening, maintenance of oral health, healthy lifestyles promotion, emphasis on increasing health literacy and emphasis on implementing integrated medical-dental care delivery provide current best practices for mitigating disease onset or progression. Emerging non-invasive technologies surrounding glycemic assessment may mitigate screening barriers in the dental setting and may be incorporated as components of effective ICMs.…”
Section: Discussionmentioning
confidence: 99%
“…To date, lifestyle intervention including pharmacological management (Table 5) and bariatric surgery in morbidly obese patients have demonstrated greatest efficacy in delaying/preventing diabetes onset in pre-diabetic individuals, achievement of glycemic control and improvement in oral indices. 65 In the absence of screening, maintenance of oral health, healthy lifestyles promotion, emphasis on increasing health literacy and emphasis on implementing integrated medical-dental care delivery provide current best practices for mitigating disease onset or progression. Emerging non-invasive technologies surrounding glycemic assessment may mitigate screening barriers in the dental setting and may be incorporated as components of effective ICMs.…”
Section: Discussionmentioning
confidence: 99%
“…Diet and regular exercise from moderate to intense can improve glucose levels in patients with T2DM and those at risk for developing obese and T2DM. Lifestyle intervention is a proven strategy for reducing diabetes incidence [14,15]. Nevertheless, the intervention is considered effective only in the short term but is difficult to adhere to in the long run, thus limiting its effectiveness.…”
Section: Non-pharmacologic Treatmentmentioning
confidence: 99%
“…The development of T2DM is a complex, multistep, and multifactorial process, involving various environmental and genetic factors. Previous studies have reported that hyperglycemia, hypertension, dyslipidemia, and increased blood sugar levels contribute to the development of this disease (Ahmadi et al, 2014;Chen, Pei, et al, 2015). However, not all individuals exposed to similar risk factors develop T2DM, suggesting that genetic variations might influence susceptibility.…”
Section: Introductionmentioning
confidence: 99%